Diverse cellular actions of tert-butylhydroquinone, a food additive, on rat thymocytes. Issue 6 (29th September 2017) - Kamemura, Norio; Oyama, Keisuke; Kanemaru, Kaori; Yokoigawa, Kumio; Oyama, Yasuo
Graphical Abstract: Abstract: Tertiary butylhydroquinone (TBHQ) is a food additive that possesses antioxidant activity. Its alternative applications have been explored in recent studies. However, there is controversy regarding safety. In this study using rat thymocytes, the cellular actions of TBHQ at sublethal concentrations were examined. TBHQ at concentrations of 3 μM or more elevated intracellular Zn 2+ concentration ([Zn 2+ ]i ) in a dose-dependent manner, by increasing membrane Zn 2+ permeability and releasing Zn 2+ from cellular stores. TBHQ at 30 μM significantly increased side scatter (cell density) and the exposure of phosphatidylserine (PS) on cell membrane surfaces. It also decreased cellular glutathione (GSH) content without affecting cell lethality. Forward scatter was attenuated by 100 μM TBHQ. Thus, it is considered that TBHQ at sublethal concentrations (30 μM or less) exerts some adverse actions on cells. TBHQ at 10–30 μM attenuated the increase in cell lethality induced by hydrogen peroxide (H2 O2 ), while potentiation of H2 O2 cytotoxicity by 100 μM TBHQ was observed. The range of concentrations of TBHQ from benefit to toxicity under in vitro conditions may be 10–30 μM. Although TBHQ exhibits antioxidative actions at concentrations that are lower than those which elicit adverse cellular effects, sublethal levels of TBHQ cause some adverse actions that may be clinically concerned.